Valences in voters’ emotional response: Experimental design with neuroscience - Dias, Carlos Magno Machado; Gonçalves, Carlos Alberto; Ribeiro, Ângela Maria (Revista de Administração da UFSM, 2020)
This work aims to quantitatively and qualitatively evaluate the valence of voters’ emotional response to changes in the scenarios in videos of political propaganda. The experiment was conducted in a laboratory with a fictitious candidate and content. We used four different scenarios: one with a completely white background, one simulating a library, one with a popular house, and one with luxury houses. We use the Facial Action Coding System (FACS) as an instrument to measure emotions. We found statistical differences between the intensity of the valences throughout the video (n=108). The work empirically demonstrated that the scenarios can enhance the emotional effects of this type of advertising.